Idealism of Traditional Convention in Arts as a basis for developing the Creation of local identity works - Wihendar; Nina Retnawati; Nida Ulhanifah Setiadi; Rindha Putri Triyuma; Siti Nur Kholisoh (Pascasarjana ISBI Bandung Conference Series, 2025)
This article emphasises about the importance of preserving the idealism of the past generation’s noble way of thinking about the fundamental values and meaning of life in traditional art creation. The creation of art is based on the convention of tradition idealism as a foundation of a work intended to become a local identity. Art creation begins with a process of gathering musical material through ethnographic studies. This matter related to the region of Cibingbin Sub-district, Kuningan Regency, West Java. The gathered musical material that is dugjring as the basic drum pattern that are in Dukuhbadag Village, and the dialect of Cibingbin community. The dialect will be adopted and adapted as a melodic basis and then designed as a work of art to be showcased in musical performance. Keywords: Dugjring; Kuningan; Traditional Conventions; Musical Performance.